(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper explores the evolution and socio-political influence of the Rashtriya Swayamsevak Sangh (RSS) over the past century. Founded in 27 September, 1925, the RSS has grown from a marginal cultural movement to a powerful ideological and organizational force in Indian politics. Through a historical lens, this study examines the RSS’s ideological foundation in Hindutva, its organizational growth, relationship with the Bharatiya Janata Party (BJP), and its pervasive influence across education, culture, and civil society. The paper also critically evaluates the RSS’s role in shaping India’s national identity, its contested legacy, and its implications for democracy and secularism.